Synthesis, Characterization and Study Some Thermal Properties of New Maleimide Polymers from Sulfadiazine - Ehab Kareem Obaid (Journal of Global Pharma Technology, 2018)
Series homo and copolymers of N-substitution maleimides by convert Sulfadiazine to chloroacetyl sulfadiazine (compound G) by mixture Sulfadiazine and chloroacetyl chloride in presence triethylamine in DMF as solvent, and then substitution of chloro group in compound G by hydrazine to prepare hydrazinyl chloroacetyl sulfadiazine (compound H), then amic acid derivative (I) were prepared by reaction malic anhydride with (compound H). This compound convert to N-substitution maleimide by closed the ring to preparation the (monomer) compound (J) by use access of acetic anhydride and sodium acetate. Finally preparation of homopolymers (K) by reaction the monomer carried out with Azobisisobutyronitrile (AIBN) as a free radical initiator in DMF as a solvent, and preparation of two different copolymers by reaction (I) compound with (acrylamide and maleic anhydride) carried out with AIBN as initiator and DMF as a solvent, and then study thermal properties of prepared polymers by TGA and DSC. All synthesized compounds were identified by many spectroscopy methods including FT-IR, 1H-NMR, 13C-NMR, and Mass spectroscopy.Keywords: Sulfadiazine, Amic acid, Maleimide, AIBN, homopolymaleimide, copolymaleimide.